SOSIALISASI UJI MAKANAN/JAJANAN MENGANDUNG BORAKS PADA WALI MURID SISWA SDIT DARUL FALAH TEBUIRENG JOMBANG - Dian Anisa Rokhmah Wati; Nur Muflihah; Nailul Izzati; Imamatul Ummah; Minto (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2022)
The misuse of borax as a food additive is still often found in food/snacks, including in the elementary school environment. Therefore, the community service team of Faculty of Engineering, Hasyim Asy'ari University took the initiative to disseminate information about the risks of borax misuse and how to detect the presence of borax in a food. This community service program aims to socialize to the public about the use of turmeric as an ingredient to test foods containing borax in a simple way. This is socialized to the public, especially the guardians of SDIT Darul Falah Cukir Jombang. The final target of this community service program activity is to increase public awareness about the importance of monitoring the food eaten by their children so that the development of children is well maintained. Based on the results of this community service, it is known that the socialization carried out could provide knowledge to the community about the meaning and importance of healthy food for student development and provide knowledge about how to test food easily, in an effective and efficient way.